Analysis of Plot of Syngeâ€™s Play â€œRider to the Seaâ€ - Siahaan, Safnidar (English Department, University of Riau Kepulauan, Batam,Indonesia, 2016)
The research offers a plot analysis in Syngeâ€™s play â€œRider to the Seaâ€. This play is written in 1902 describing a complex family life story. This play will be analyzed by using the structure method focusing on the plot development of the play. The story of the play